A second-generation combined linkage–physical map of the human genome - Matise, Tara C.; Chen, Fang; Chen, Wenwei; De La Vega, Francisco M.; Hansen, Mark; He, Chunsheng; Hyland, Fiona C.L.; Kennedy, Giulia C.; Kong, Xiangyang; Murray, Sarah S.; Ziegle, Janet S.; Stewart, William C.L.; et al. (Genome Research, 2007)
We have completed a second-generation linkage map that incorporates sequence-based positional information. This new map, the Rutgers Map v.2, includes 28,121 polymorphic markers with physical positions corroborated by recombination-based data. Sex-averaged and sex-specific linkage map distances, along with confidence intervals, have been estimated for all map intervals. In addition, a regression-based smoothed map is provided that facilitates interpolation of positions of unmapped markers on this map. With nearly twice as many markers as our first-generation map, the Rutgers Map continues to be a unique and comprehensive resource for obtaining genetic map information for large sets of polymorphic markers.
10.1101/gr.7156307